2011
DOI: 10.1097/jto.0b013e31822956e8
|View full text |Cite
|
Sign up to set email alerts
|

A Noninvasive System for Monitoring Resistance to Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors with Plasma DNA

Abstract: The MBP-QP method is simple, sensitive, and-intriguingly-reflective of clinical course, compared with the other three mutation-detection systems. Thus, the MBP-QP method is an ideal noninvasive monitoring system for detecting T790M in plasma samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 32 publications
6
63
0
1
Order By: Relevance
“…v‐Raf murine sarcoma viral oncogene homolog B1 (BRAF) mutations were identified on LBC material from TC with high reproducibility, feasibility, and informative results 42. LBC specimens were also used to determine the physical status of HPV DNA by in situ hybridization (ISH) and HPV genotyping by polymerase chain reaction (PCR) for identifying patients at high risk of cervical carcinoma43 and of epidermal growth factor receptor (EGFR) mutation for lung carcinoma 44. To search for immunoglobulin gene arrangements, using PCR for ML was reported to be possible with LBC specimens 45.…”
Section: Discussionmentioning
confidence: 99%
“…v‐Raf murine sarcoma viral oncogene homolog B1 (BRAF) mutations were identified on LBC material from TC with high reproducibility, feasibility, and informative results 42. LBC specimens were also used to determine the physical status of HPV DNA by in situ hybridization (ISH) and HPV genotyping by polymerase chain reaction (PCR) for identifying patients at high risk of cervical carcinoma43 and of epidermal growth factor receptor (EGFR) mutation for lung carcinoma 44. To search for immunoglobulin gene arrangements, using PCR for ML was reported to be possible with LBC specimens 45.…”
Section: Discussionmentioning
confidence: 99%
“…Exon 19 deletions and point mutations including L858R and T790M were detected by the wild inhibiting PCR and quenched probe (WIP-QP) system and the MBP-QP system, respectively. These systems were fully automated using i-densy™ IS-5320 (ARKRAY Inc., Kyoto, Japan), as described previously (28,30,32). Briefly, WIP-QP consisted of wild inhibiting PCR (WIP) and quenched probe (QP) systems, as described previously (32).…”
Section: Methodsmentioning
confidence: 99%
“…As the system utilizes peripheral blood, it is possible to examine T790M repeatedly. Our previous retrospective study using the MBP-QP system demonstrated that T790M was detected in 53-56% of patients who acquired resistance to EGFR-TKI (28,29). In addition, a prospective multicenter observational study was then performed to determine whether T790M detection using MBP-QP system with plasma DNA was useful for monitoring acquired resistance to EGFR-TKI, and T790M was reproducibly detected in 40% of patients whose disease became progressive (30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empfindliche und qualitativ hochwertige Methoden zeigen, dass cfDNA bei Tumorpatienten zu einem gegenüber anderen Diagnostikmodalitäten früheren Nachweis von Rezidiven und Entwicklungen von Therapieresistenz führt [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Die Analyse der ctDNA besitzt damit ein wichtiges Potenzial für die frühere Identifikation von Therapieversagern, wie sie zum Beispiel während der Therapie des metastasierten kolorektalen Karzinoms mit anti-EGFR Antikörpern auftreten.…”
Section: Introductionunclassified